Russian experience in using of digital technologies in the electoral process - Shaposhnikov, Alexey V. (Journal of the Belarusian State University. Law, 2024)
Digital technologies are an integral part of all spheres of life in modern Russian society, including the political sphere. Their application is aimed at observing the basic constitutional principles and freedoms of Russians within the framework of the latter’s will on significant political issues. This article is devoted to the Russian Federation’s study of the experience in the field of using of digital technologies in the electoral process. The author has analysed in detail various approaches to defining of the concept «electoral process», highlighted the basic constitutional principles of the political will of citizens, consistently analysed and summarised the digital technologies used in the Russian Federation within the framework of organising and conducting elections. The study of Russian Federation’s experience in the use of digital technologies in the electoral process was carried out in line with constitutionalism. Certain elements of the constitutionalisation of the electoral system in Russia, which is the key to holding fair elections, are enshrined in the Constitution of the country.